Mechanisms of Formation of Media Images and Stereotypes - Zarnigor Umid kizi, Jumayeva (The Lingua Spectrum, 2026)
Contemporary media environment, particularly social networks, television, cinema, and the advertising industry, plays a significant role in the formation and reinforcement of stereotypes in society. Media representations are often simplified, generalized, and one-sided, which leads to a distorted perception of social reality among audiences. As a result, stereotypes related to gender, age, social status, and ethnic groups are strengthened. The main problem is that media representations do not fully reflect the real diversity of society but instead reconstruct it through stereotypical images, thereby shaping ideological perceptions in the audience’s consciousness. This study aims to scientifically examine the role of media representations in stereotype formation and to systematically analyze the mechanisms of stereotype development. Framing, repetition, and social comparison mechanisms are analyzed separately in this study. In addition, the practical manifestation of these processes is demonstrated through examples from advertising and film. The results of the study indicate that media representations actively participate in the formation and dissemination of stereotypes in society. They not only reflect reality but also reconstruct it and interpret it within certain ideological frameworks.